The Backgrounds Of Female Student's Enrollment At The Mathematics Education Department Of Muhammadiyah University Of Surakarta - Nugroho, Zuhdha Basofi; , Idris Harta, M.A., Ph.D (2013)
The purpose of this research is to describe: (1) the perception of prospective female students before enroll at the Mathematics Department of UMS, (2) the background of female students enroll at the Mathematics Education Department of UMS. The kind of this study is descriptive qualitative research. The subject in this study is the female students in 2011 academic year at the mathematics education department of Muhammadiyah University of Surakarta. Methods of collecting data used in this study are questionnaire, interview, and observation. Data analysis techniques used in this research is the analysis of qualitative data, with Miles and Huberman models. Validity of data used is triangulation technique. The conclusions of this research are: (1) Prospective student perceptions about mathematics education department of UMS are already good. Because they saw the accreditation of B and there are many interested person to enrol at mathematics education department of UMS. In addition, the score of test in one day service to enrol at mathematics education department of UMS are also high. (2) There are many factors that influence female students enroll at mathematics department of UMS namely, interest, ideals, religion, ability, others people influence, cost, certain situation, and prospect